Perception towards service quality and the impact of brand image on customers in Prudential BSN Takaful Berhad,Melaka / Nur Ain Farhana Sulaiman and Nurul Najwa Khairul Azman - Sulaiman, Nur Ain Farhana; Khairul Azman, Nurul Najwa (2015)
The title of this study is “Perception towards service quality and The Impact of Brand Image on Customers in Prudential BSN Takaful Berhad Melaka”. The first purpose of this study is to determine the level of brand image towards Prudential BSN Takaful Berhad Melaka. There are five independent variables involved in this study which are Tangible, Reliability, Responsiveness, Assurance and Empathy. In order to completing this study, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between those independent variables with brand image. A total of 150 peoples have participated in this study as respondents. The methodology used for the study was primary data collection. For primary data, the researcher was used the method of questionnaire to obtained through the analyzing and interpret data of result. The reliability test, regression, frequency analysis, descriptive testing and Pearson’s correlation coefficient testing was used for data analysis. From correlation testing, the result shows that one of the independent variables which is responsiveness has a strong relationship with brand image. The relationship of brand image with other independent variables which are assurance and empathy are moderate relationship while tangible and reliability are weak relationship respectively. For hypothesis, there are clearly shown that all of the hypothesis including tangible, reliability, responsiveness, assurance and empathy are supported.